2011
DOI: 10.2174/1745017901107010097
|View full text |Cite
|
Sign up to set email alerts
|

AUTISM Spectrum Disorders and Suicidality

Abstract: The paper describes the suicidal ideation and behavior in a series of 26 adult psychiatric patients affected by Autism Spectrum Disorders (ASDs), the clinical features and the psychiatric comorbidity of patients presenting suicidal behavior, and the history of suicide or suicide attempt in their relatives. Two (7,7%) patients committed suicide. One (3.8%) patient attempted suicide twice, and one (3.8%) patient self-harmed by cutting his face and one finger of his hand with a razor. Eight (30.8%) patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 18 publications
2
37
0
2
Order By: Relevance
“…Nearly half of the adults with ASD with a diagnosis of attempted suicide did not also have a diagnosis of depression, suggesting that depression may be underdiagnosed in the autistic population, resulting in lack of needed treatment. Our findings are consistent with the few previously published studies of suicidal ideation and attempt among small clinical samples of individuals with ASD (Raja, Azzoni et al 2011;Mayes, Gorman et al 2013;Storch, Sulkowski et al 2013;Cassidy, Bradley et al 2014;Paquette-Smith, Weiss et al 2014), which reported rates in the range of 11%-40%. The rate in our study (1.8%) was substantially lower, likely because it reflected suicide attempts only (not ideation) in a 5-year period, and not lifetime experiences.…”
Section: Discussionsupporting
confidence: 93%
“…Nearly half of the adults with ASD with a diagnosis of attempted suicide did not also have a diagnosis of depression, suggesting that depression may be underdiagnosed in the autistic population, resulting in lack of needed treatment. Our findings are consistent with the few previously published studies of suicidal ideation and attempt among small clinical samples of individuals with ASD (Raja, Azzoni et al 2011;Mayes, Gorman et al 2013;Storch, Sulkowski et al 2013;Cassidy, Bradley et al 2014;Paquette-Smith, Weiss et al 2014), which reported rates in the range of 11%-40%. The rate in our study (1.8%) was substantially lower, likely because it reflected suicide attempts only (not ideation) in a 5-year period, and not lifetime experiences.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical literature also documents cases of deliberate self-harm (Balfe & Tantam, 2010;Wing 1981;Wolff & Chick, 1980) and suicidal ideation (Clarke, Littlejohns, Corbett & Joseph, 1989;Raja, Azzoni & Frustaci, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the prevalence of bipolar disorder is higher in individuals with ASD (6% to 21%) [100] than in the general population (2.4%) [101]. Furthermore, some studies reported that the proportion of bipolar disorder together with psychotic symptoms was 7% in adult patients with ASD [35] and 23% in adult patients with ASD in psychiatric intensive care units [102]. Therefore, if clinicians encounter a patient with a history of repetitive depressive episodes together with occasional manic/mixed/ psychotic periods, they should suspect an underlying ASD diagnosis (especially a patient with an early onset age of mood episodes [103]).…”
Section: Asd and Mood Disordersmentioning
confidence: 99%